WNT3A‐loaded exosomes enable cartilage repair. Issue 7 (19th May 2021) - Thomas, Bethan L.; Eldridge, Suzanne E.; Nosrati, Babak; Alvarez, Mario; Thorup, Anne‐Sophie; Nalesso, Giovanna; Caxaria, Sara; Barawi, Aida; Nicholson, James G.; Perretti, Mauro; Gaston‐Massuet, Carles; Pitzalis, Costantino; et al.
Abstract: Cartilage defects repair poorly. Recent genetic studies suggest that WNT3a may contribute to cartilage regeneration, however the dense, avascular cartilage extracellular matrix limits its penetration and signalling to chondrocytes. Extracellular vesicles actively penetrate intact cartilage. This study investigates the effect of delivering WNT3a into large cartilage defects in vivo using exosomes as a delivery vehicle. Exosomes were purified by ultracentrifugation from conditioned medium of either L‐cells overexpressing WNT3a or control un‐transduced L‐cells, and characterized by electron microscopy, nanoparticle tracking analysis and marker profiling. WNT3a loaded on exosomes was quantified by western blotting and functionally characterized in vitro using the SUPER8TOPFlash reporter assay and other established readouts including proliferation and proteoglycan content. In vivo pathway activation was assessed using TCF/Lef:H2B‐GFP reporter mice. Wnt3a loaded exosomes were injected into the knees of mice, in which large osteochondral defects were surgically generated. The degree of repair was histologically scored after 8 weeks. WNT3a was successfully loaded on exosomes and resulted in activation of WNT signalling in vitro. In vivo, recombinant WNT3a failed to activate WNT signalling in cartilage, whereas a single administration of WNT3a loaded exosomes activated canonical WNT signalling for at least one week, and eight weeks later, improved the repair of osteochondral defects. WNT3a assembled on exosomes, is efficiently delivered into cartilage and contributes to the healing of osteochondral defects.